PENINGKATKAN MUTU PENDIDIKAN MELALUI BUDAYA ORGANISASI DI SD MUHAMMAD AL-UNAIZY CISAAT SUKABUMI - Dede Maulana Malik Dede (Fakultas Agama Islam Universitas Islam Jakarta, 2023)
This study aims to reveal clearly about improving the quality of education through an organizational culture approach. The role of organizational culture in an organization is to improve performance, commitment of organizational members, and create an atmosphere of kinship, collaboration, resilience in learning, enthusiasm for moving forward, encouragement to work hard, and not easily complain. This will then form a conducive culture for the organization, such as the creation of a professional culture, positive culture, open culture and a pleasant atmosphere among the members of the organization. By creating a conducive organizational culture, it will be very easy to improve the quality of education in an educational institution. This study uses qualitative methods using anthropological approaches and organizational theory. Data collection through observation, in-depth interviews, and document analysis. Testing the validity of the data through continuous observation and triangulation of sources and methods. Data analysis uses an interactive model, including; data collection, data reduction, data presentation and taking conclusions. The results of the study show that the organizational culture at Muhammad Al-Unaizy Elementary School greatly supports the improvement of the quality of education. The elements of organizational culture, namely: (1) the basic assumptions manifested in the history, vision, mission, goals and symbols of the school. (2) organizational values ​​are manifested by a quality culture, such as; understanding the meaning of history, vision, mission, goals and symbols, then forwarded to the implementation of quality-oriented processes, services, environment and human resources. The culture of discipline applied by madrasah residents contributes to improving the character of madrasah residents to obey the rules even though there are still 10-15% of students who lack discipline. The culture of hard work that is implemented aims to enable school residents to provide maximum performance. (3) artifacts that can be seen from the physical condition of the building, the environment and the uniforms used by students are visible cultural elements. The leadership factor of the madrasa head, physical conditions and infrastructure, the existence of rules and regulations are factors supporting organizational culture at Muhammad Al-Unaizy Elementary School, while students' lack of understanding of the history, vision, mission and objectives of the madrasa, lack of harmony in the relationship between teachers and utilization of facilities Infrastructure that is less than optimal and the centralization of funds on the part of the foundation are factors inhibiting organizational culture in improving the quality of education at Muhammad Al-Unaizy Elementary School.